THE CONTRIBUTION OF ISLAMIC KINGDOMS TO THE DEVELOPMENT OF ISLAMIC JUDICIARY IN INDONESIA: HISTORICAL LEGAL APPROACH ANALYSIS - Muhammad Fazlurrahman Syarif; Muhammad Syauqi Bin-Armia (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2022)
Islamic kingdoms in Indonesia have played significant roles in spreading and enforcing Islamic law. Each kingdom has a judge from an Islamic school in the Islamic judiciary process. If the cases are difficult to adjudicate, the court invites other Islamic scholars from other kingdoms to give their opinion on the cases. Islamic scholars have habitually written books to be used by further Islamic scholars. Although Islamic kingdoms have shared their experiences and knowledge, the implementation of Islamic law has still been different even though decisions tended to find their way to justice. For instance, in family law cases, the verdicts could be different, considering the customary law established in each kingdom. This article utilizes a historical legal approach to analyze the data from historical documents in Indonesia. The Islamic court in Indonesia has grown from the court in the time of Islamic kingdom, including Islamic family law. However, the present-day Islamic court has developed further than it was in the time of Islamic kingdom in Indonesia. Thus, the 4.0 era has also affected the judiciary process. Abstrak: Kerajaan-kerajaan Islam di Indonesia telah memainkan peran penting dalam menyebarkan dan menegakkan hukum Islam. Setiap kerajaan memiliki hakim dari sekolah Islam dalam proses peradilan Islam. Jika kasusnya sulit untuk diadili, pengadilan mengundang ulama Islam lainnya dari kerajaan lain untuk memberikan pendapat mereka tentang penyelesaian kasus tersebut. Cendekiawan Islam memiliki kebiasaan menulis buku yang digunakan untuk sarjana Islam selanjutnya. Meskipun di antara kerajaan-kerajaan Islam telah berbagi pengalaman dan pengetahuan, penerapan hukum Islam masih berbeda, meskipun cenderung mencari jalan menuju keadilan. Misalnya, dalam kasus hukum keluarga putusannya bisa berbeda, mengingat hukum adat yang dipraktekkan dalam suatu kerajaan. Artikel ini menggunakan pendekatan hukum historis untuk menganalisis data dari dokumen sejarah di Indonesia. Peradilan Islam di Indonesia memiliki keterkaitan dengan peradilan pada masa kerajaan Islam, termasuk hukum keluarga Islam. Akan tetapi Peradilan Islam saat ini lebih berkembang dibandingkan pada masa kerajaan Islam di Indonesia; salah satu penyebabnya adalah era 4.0 juga mempengaruhi proses peradilan. Kata Kunci: Kontribusi Kerajaan Islam, Peradilan Islam Di Indonesia, Pendekatan Hukum Historis